Exploring the Effectiveness of Modern Agricultural Technology for Farmers for the Green Revolution - Espinueva, Jennelyn; Oy, Sovanborey; Var, Sophal (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine the extent of effectiveness of modern agricultural technology among farmers. Methodology: This research employs a quantitative descriptive method to assess farmers' perceptions and experiences in utilizing modern agricultural technology. Data were collected through surveys distributed to selected farmers in Barangay Butong. The gathered data were analyzed using statistical tools to determine the level of effectiveness and the correlation between demographic factors and technology adoption. Main Findings: The results indicate that while modern agricultural technology has contributed to improved farming practices, its effectiveness is still influenced by farmers' knowledge, financial capacity, and access to support services. The study found a low positive correlation between age and family income with the effectiveness of modern agricultural technology, whereas gender showed a very low negative correlation. These findings suggest that while technology provides potential benefits, its impact is not uniform among farmers. Novelty/Originality of this study: The novelty of this study lies in its localized assessment of modern agricultural technology's effectiveness, focusing on Barangay Butong. Unlike previous studies that examine broader agricultural trends, this research provides insights into specific barriers and opportunities faced by small-scale farmers in adopting technological advancements.